AB059. MiR-34a inhibits cell proliferation in prostate cancer by downregulation of SIRT1 expression - Ge, Yongchao (Transl Androl Urol, 2016)
OBJECTIVE: MicroRNA-34a (miR-34a) is a tumor suppressor gene, which inhibits abnormal cell growth by regulating the expression of other genes. However, the role of miR-34a regulation sirtuin 1 (SIRT1) in prostate cancer is not clear. The objective of this study was to investigate the biological function and molecular mechanisms of miR-34a regulation SIRT1 in human prostate cancer PC-3 cell. METHODS: Fresh prostate tissues were obtained, and the miR-34a expression in prostate cancer tissues was measured using quantitative real-time PCR (qRT-PCR). qPCR and Western blotting were performed to assess the over-expression of miR-34a regulated SIRT1 expression in PC-3 cells, and the cell growth was tested by Cell Counting Kit-8 (CCK-8). Flow cytometry was used to detect cell cycle. RESULTS: The miR-34a expression levels in prostate cancer tissues were significantly decreased as compared with adjacent normal prostate tissues (P<0.05). SIRT1 expression levels in PC-3 cells with over-expression of miR-34a were significantly lower than those in the negative control (P<0.05). The over-expression of miR-34a inhibited PC-3 cells growth and resulted in cells cycle arrest compared with the negative control (P<0.05). CONCLUSIONS: In conclusion, miR-34a inhibits the human prostate cancer cell proliferation, in part, through downregulation of SIRT1 expression.